Formulasi dan Uji Aktivitas Antibakteri Sediaan Mouthwash Ekstrak Daun Mengkudu (Morinda Citrifolia L.) Terhadap Bakteri Streptococcus Mutans - Najwa Nadzira; Rahmadani Rahmadani; Dinda Sari Utami; Zulmai Rani (Universitas Pahlawan Tuanku Tambusai, 2026)
Dental caries and halitosis are oral health issues largely caused by Streptococcus mutans. Noni leaves (Morinda citrifolia L.) contain bioactive compounds with potential antibacterial properties, making them suitable for formulation into a mouthwash. This study aimed to formulate an ethanolic extract of noni leaves into a mouthwash and evaluate its antibacterial activity against Streptococcus mutans. The study was conducted experimentally, involving extract preparation, phytochemical screening, mouthwash formulation at concentrations of 10%, 15%, and 30%, physical evaluation of the preparations, and antibacterial activity testing using the disc diffusion method. The research results indicate that all formulas met physical evaluation requirements and exhibited antibacterial activity. The 30% formula produced the greatest inhibitory effect, with an average inhibition zone of 20.15 mm, followed by the 15% formula (18.23 mm) and the 10% formula (15.23 mm). Thus, the ethanolic extract of noni leaves can be formulated into a mouthwash that is stable and effective in inhibiting the growth of Streptococcus mutans. Keywords: Morinda citrifolia L., mouthwash, antibacterial activity, Streptococcus mutans.